Investigation on the effect of Si addition to the high temperature cyclic oxidation behaviour of β-NiAlDy alloy used in advanced jet engine applications. (2021) - Saminathan, Rajasekaran; Ali Fageehi, Yahya; Ramalingam, K.B.; Vidhya, D.; Bhuvaneshwari, D.; Bala Muthu Manickam, R.; Lokesh kumar, P.; Vasudevan, AnguRaj
Abstract: This work concentrates on the study of the effect of addition of Si to the β-NiAlDy alloy in improving its cyclic oxidation behaviour at high temperature namely 1000 0 C. Silicon addition of 1%, 3% and 5% are carried out to prepare β-NiAlDy alloy groups by arc-melting and further by casting in inert atmosphere. The prepared alloy groups were further subjected to annealing in vacuum at temperature namely 1100 0 C for a time period of 12 h. These alloy groups are subjected to cyclic oxidation tests up to 100 cycles with each cycle time duration of 5 h of atmospheric exposure at aforementioned temperature. The oxidation behaviour of the alloy groups were studied in detail by carrying out cyclic oxidation measurements, XRD, SEM and EDAX analysis. The results clearly show the variation of oxidation behaviour of the β- NiAlDy alloy when Si content is increasing from 1 to 5%. It is registered that the oxidation resistance of β-NiAlDy increase to a greater extent when 1 to 5% Si is added to the alloy.